12/15-Lipoxygenase-Derived Lipid Metabolites Induce Retinal Endothelial Cell Barrier Dysfunction: Contribution of NADPH Oxidase - Amira Othman (380131) (2013)
The purpose of the current study was to evaluate the effect of 12/15- lipoxygenase (12/15-LOX) metabolites on retinal endothelial cell (REC) barrier function. FITC-dextran flux across the REC monolayers and electrical cell-substrate impedance sensing (ECIS) were used to evaluate the effect of 12- and 15-hydroxyeicosatetreanoic acids (HETE) on REC permeability and transcellular electrical resistance (TER). Effect of 12- or 15-HETE on the levels of zonula occludens protein 1 (ZO-1), reactive oxygen species (ROS), NOX2, pVEGF-R2 and pSHP1 was examined in the presence or absence of inhibitors of NADPH oxidase. In vivo studies were performed using Ins2Akita mice treated with or without the 12/15-LOX inhibitor baicalein. Levels of HETE and inflammatory mediators were examined by LC/MS and Multiplex Immunoassay respectively. ROS generation and NOX2 expression were also measured in mice retinas. 12- and 15- HETE significantly increased permeability and reduced TER and ZO-1expression in REC. VEGF-R2 inhibitor reduced the permeability effect of 12-HETE. Treatment of REC with HETE also increased ROS generation and expression of NOX2 and pVEGF-R2 and decreased pSHP1 expression. Treatment of diabetic mice with baicalein significantly decreased retinal HETE, ICAM-1, VCAM-1, IL-6, ROS generation, and NOX2 expression. Baicalein also reduced pVEGF-R2 while restored pSHP1 levels in diabetic retina. Our findings suggest that 12/15-LOX contributes to vascular hyperpermeability during DR via NADPH oxidase dependent mechanism which involves suppression of protein tyrosine phosphatase and activation of VEGF-R2 signal pathway. Other Information Published in: PLoS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0057254 Additional institutions affiliated with: College of Science - QU (1977-2004/2005), College of Arts and Sciences - QU (2004/05-2016).